Crystallinity in quasi-alternating cycloolefin copolymers: Overcoming brittleness - Moon, Seung Hyun; Park, Kyung Lee; Baek, Jun Won; Lee, Hyun Ju; Choi, Ji Hwan; Lee, Yeonju; Lee, Bun Yeoul (Journal of Polymer Science, 2020)
Cycloolefin copolymers (COCs, which are produced via ethylene/cycloolefin copolymerization) and cycloolefin polymers (COPs, which are synthesized by a rather complicated two-step process via ring-opening metathesis polymerization and subsequent hydrogenation) are commercialized materials used especially widely in optical applications. Although a COP can be used after processing into a film, films made from conventional COCs are too brittle. Optical-grade COCs and COPs are generally known as amorphous polymers. By contrast, here, a quasi-alternating ethylene/norbornene copolymer (norbornene content 56 mol%), prepared from a constrained-geometry Hf complex, shows some melting (Tm) signals in a broad temperature range (150–200°C) in the first heating scan of differential scanning calorimetry (DSC) when the samples are prepared by precipitation from a toluene solution. In the second heating scan, only glass transition (Tg) signals are observed at ~140°C with disappearance of Tm signals. The quasi-alternating ethylene/norbornene copolymer has better mechanical properties (greater elongation at break) than random congeners, which do not show any melting signal, though elongation at break is still inferior to that of the COP which shows the melting signal in the first heating scan of DSC. The enhanced mechanical properties of the quasi-alternating ethylene/norbornene copolymer and commercial-grade COP may be ascribed to semicrystallinity observed in the first heating scan.
Keywords: Amorphous polymers; Broad temperature ranges; Constrained geometry; Cyclo-olefin polymers; Cycloolefin copolymers; Elongation at break; Optical applications; Ring opening metathesis polymerization; alternating copolymer; brittleness; cycloolefin copolymer; differential scanning calorimetry; semicrystallinity